2013
DOI: 10.1002/adsc.201200983
|View full text |Cite
|
Sign up to set email alerts
|

Facile Reduction of Nitroarenes into Anilines and Nitroalkanes into Hydroxylamines via the Rapid Activation of Ammonia⋅ Borane Complex by Supported Gold Nanoparticles

Abstract: Gold nanoparticles supported on titania catalyse, even at a ppm loading level, the quantitative reduction of nitroarenes into anilines and nitroalkanes into alkylhydroxylamines by the ammonia· borane complex. No dehalohalogenation was seen in the case of chloro-or bromonitroarenes, while ester, cyano, or carboxylic acid functionalities also remain intact. The nitroarene to aniline reduction pathway does not require nitrosoarenes as intermediate products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
50
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 77 publications
(55 citation statements)
references
References 71 publications
1
50
0
1
Order By: Relevance
“…Other amino-nitrobenzenes (20 and 22) were reduced similarly to 1,3-dinitrobenzene, producing the corresponding diamine products (Table 1, entries 11 and 12). The selective reduction of -NO 2 was better demonstrated in aromatic compounds bearing other reducible substituents such as 1-bromo-4-nitrobenzene (24) and methyl 2-hydroxy-4- nitrobenzoate (26). They were all reduced to the related amine products (>99% conversion in 5 min) ( Table 1, entries 13 and 14), and the Br-or ester group showed no obvious effect on the NO 2 reduction kinetics.…”
Section: Resultsmentioning
confidence: 99%
“…Other amino-nitrobenzenes (20 and 22) were reduced similarly to 1,3-dinitrobenzene, producing the corresponding diamine products (Table 1, entries 11 and 12). The selective reduction of -NO 2 was better demonstrated in aromatic compounds bearing other reducible substituents such as 1-bromo-4-nitrobenzene (24) and methyl 2-hydroxy-4- nitrobenzoate (26). They were all reduced to the related amine products (>99% conversion in 5 min) ( Table 1, entries 13 and 14), and the Br-or ester group showed no obvious effect on the NO 2 reduction kinetics.…”
Section: Resultsmentioning
confidence: 99%
“…nitrostyrene, nitrobenzaldehydes and nitrobenzonitriles, was thus successfully accomplished. Other authors showed later that the reaction could be carried out under milder conditions using alternative and more efficient reductants as the ammonia-borane complex [7], sodium borohydride [8], isopropanol [9], silanes [10], CO/H 2 O [11] (WGS reaction as source of dihydrogen). Intriguingly UV-Vis light irradiation of the AuNPsTiO 2 catalysts produced the selective reduction of nitrobenzenes to azobenzenes [12].…”
Section: Introductionmentioning
confidence: 99%
“…Issues of sustainable production and safe handling are now drivers for alternative sources of hydrogen and/or hydrogen donors. Several hydrogen carriers including hydrazine [3], ammonia-borane complexes [4], esters [5], alcohols [6] and acids [7] have been employed in homogeneous and heterogeneous transfer hydrogenation but application is hampered due to the required separation steps for catalyst reuse. A continuous heterogeneous catalytic system that combines dehydrogenation with hydrogen release that is utilised in hydrogenation represents an alternative approach that circumvents the requirement for an external hydrogen supply.…”
Section: Introductionmentioning
confidence: 99%